EFL TEACHERS' ROLES IN TECHNOLOGY-INTEGRATED INSTRUCTION PRACTICES - Anisatul Karimah, - (2019)
Since 1990s the world citizens have been facing a rapid progress in technology and digital development. This development influences all life aspects including educational area. For teachers, one of ways to be able to effectively and efficiently cope with millennial students is through technology integration within classroom practices. While technology can assist and/or accomplish most duties teachers need to do, they need to explore more on how they can act in instructional context to sustain their existence and cope with existing challenges in technology-integrated instruction (TII). While much research focuses on practices, benefits, opportunities, and challenges, only a little pays attention to teachers' role in TII. Moreover, much of the existing research has not addressed teachers' roles in TII within English as a foreign language (EFL) context. This study describes teachers' reasons of technology integration and selection, and explores their roles within TII framework especially in the context of junior secondary school English classroom in Indonesia. The participants were selected purposively to those who had adequately thorough experience on utilizing digital technologies to support EFL teaching. Lesson plan analysis, observation, and interview were conducted to collect relevant data. Findings show that teachers' considerations in technology integration are driven by pedagogical purposes and rooted from current social phenomena especially those addressing technology advancement. Meanwhile, factors contributing to technology selection process are based on curricular, technological, and institutional factor respectively. Regarding teachers' roles within TII, it can be concluded that most of teachers' roles are getting extended as each of these roles attempts to accommodate technological matter which previously was not taken into account. Only in several sub categories of cognitive roles do they become narrower as technologies replace some of teachers' duties. Teachers also voice out their concerns related to TII in English language teaching (ELT). First, technological skills should not outweigh or shift the learning focus on the subject knowledge; second, TII in its best employment can assist students to appreciate their learning process more; and third, teachers have to be ready with plan B as most TII contexts in Indonesia have not been able to provide stable and reliable facilities.